Pregnancy and hepatitis B virus infection - Cabezas Sánchez, César (2015)
Hepatitis B virus is a double-chain DNA virus pertaining to the Hepadnaviridae family that primarily infects the liver. It is 100 times more infectious tan the human immune deficiency virus. It is found en blood and body fluids and is capable to remain active over a week in dry blood. We review hepatitis B virus infection during pregnancy and fetal and newborn repercussion.